PO077 Evaluating a nurse-led diagnosis pathway in parkinson's disease. (1st December 2017) - Robinson, Anya; Pearson, Emma; Murphy, Fiona; Davis, Jane; Carroll, Camille
Abstract : Objective: To evaluate patient satisfaction with a nurse-led new-diagnosis patient pathway for Parkinson's disease. Background: Receiving a diagnosis of Parkinson's disease can result in patients feeling vulnerable and alone. Our patient-led diagnosis project group has previously identified areas of deficiency and developed and implemented a new nurse-led patient pathway covering the first year post-diagnosis. In this project we aimed to evaluate patient experience of this patient pathway. Methods: A questionnaire was designed to evaluate whether the pathway was meeting objectives, and delivered to 40 patients diagnosed within the new pathway between March and September 2016. Results: 19 responses were received (response rate 38.7%). 100% of patients felt they were fully involved in their treatment decisions; 95% felt that treatment was tailored to their needs; 89% of patients had access to information pre-appointment and knew to bring a partner; 100% of patients were given written information during the appointment; 100% of patients felt supported in their diagnosis; 100% said they were given a point of contact and 88% of patients eligible for clinical research were offered the opportunity. Conclusion: Compared with prior to the new pathway, there is a dramatic increase in patient satisfaction. Cost-effectiveness of the pathway is currently being evaluated.